The Foundation of ESCR (Economic Social and Cultural Ritghs) in the in the Processes of Transitional Justice: Contribution to a Legal Epistemology of Human Suffering - Madrid Pérez, Antonio (2015)
In this paper, we study the reasons for the introduction of social, economic and cultural rights in transitional justice processes. This study, which will focus on the right to property and land, is part of a wider reection field: the relationship between legal epistemology and the suffering of the people derived, at least in part, political structures -legal, military, economic or administrative-. Through the study of the presence of social, economic and cultural rights intransitional processes, shows there levance of the use of one or another legal epistemology on the causes of the suffering of the people.